(untitled) (West African Journal on Sustainable Development, 2024)
The study looked at Economic and Developmental Potentials of Textile Industry for Sustainable Development of South East Region, the challenges, markets and other variables. The study employed descriptive qualitative method to arrive at the conclusion. The present decline in oil revenue and the debt burden to the Nigerian economy, it has become imperative for regional efforts towards textile industry for development. Historically, Aba and Onitsha have remained the hubs of garments making and marketing in the Southeast attracting patrons from far and wide. The clothing and textile consumption is very high in the region owing to the high fashionable tendencies of many inhabitants of zone, apart from conventional clothing consumptions; there are other special uses of clothing such as security and military uniforms, political rallies, cultural and end of the year carnivals, sporting activities, environmental remediation, building construction etc. Despite the tremendous economic potentials of the sector, the government policies over the years had negated its growth. The paper believes that with the famed entrepreneurial capability of people of Southeastern Nigeria, textile industry will certainly provide a sustainable development in the region in particular and Nigeria in general if properly harnessed.